ANALISIS PEMASARAN KARET DI KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Sutaryadi Sutaryadi; Evy Maharany; Ermi Tety (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
Batang Cenaku District is one of the sub-districts with the largest rubber plantation area and also the center for rubber production in Indragiri Hulu Regency. Smallholder rubber marketing in Batang Cenaku District is carried out by collecting traders and large traders so that the farmers get low or less profitable income. The purpose of this research is to identify rubber marketing channels, analyze the structure of the rubber market, analyze the behavior of the rubber market, and analyze the market appearance in Batang Cenaku District, Indragiri Hulu Regency. The results show that the rubber marketing in Batang Cenaku District has one type of marketing channel consisting of farmers, collectors and wholesalers, and rubber factories. The market structure in Batang Cenaku sub-district leads to an oligopoly market for the collector trader level with a concentration ratio value (Cr4) of 37.84% and a herfindahl index value of 0.09 (0 <IH <1). Meanwhile, at the wholesaler level there is only one large trader, so the market structure at the wholesaler level is a monopoly market. The behavior of the rubber market in Batang Cenaku District shows that the results of the correlation analysis between prices at the farm and factory level are 0.99, which means that there is a strong relationship between the two prices while the price transmission elasticity value is 1.27 which means that the price change at the farm level is greater than the price change. at the factory level. The appearance of the rubber market in Batang Cenaku District shows that rubber marketing at the collector and wholesaler levels is efficient with efficiency values of 11.37% and 8.02%, respectively.